Między Koreą i Europą. O dramaturgii filmów Kim Ki-duka - Domalewski, Adam (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2015)
Between Korea and Europe. The Dramaturgy of Films by Kim Ki-duk The article attempts to point out how Korean director Kim Ki-duk constructs the dramaturgy of his films. His works belong to the European art cinema tradition, and are marked by specific narrative structures and strategies (e.g. chronological order of events, parallel and mirror plot schemes, silent characters and limitation of film dialogue). Dramaturgically significant are also repeating scenes of violence and cruelty, characteristic for Kim. Finally, briefly presented are critical approaches to his films, which together with the director’s biography allow us to call him “an accented filmmaker” (using terms and concepts proposed by Hamid Naficy).